PENERAPAN TEORI BIOPHILIC DESIGN DALAM STRATEGI PERANCANGAN SEKOLAH ALAM SEBAGAI SARANA PENDIDIKAN DASAR DI KARANGANYAR - Annisa Hadny; Rachmadi Nugroho; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2017)
The quality of Indonesia's education in the international rankings is ranked low compared to other countries. On the other hand Indonesia has the potential of nature that can be utilized as a learning method that is with the natural school with nature as a medium of teaching. The use of biophilic design theory becomes important in order to create a natural school environment that can support a good learning atmosphere for learners later. This study aims to determine how appropriate design criteria for designing a planned natural school with biophilic design theory are used. The method used is to study the literacy of the theory and determine the appropriate theory to be used in the design strategy ranging from site selection, site processing, space processing and space quality, mass formation and mass management, and determining the appearance of buildings. Biophilic design design method and process of analysis that is done to produce natural school design design that can optimize the learning process in it.